Real Power Loss Reduction and Voltage Stability Enhancement by Stock Exchange, Product Demand-Availability, Affluent and Penurious Algorithms - Kanagasabai Lenin (Journal of ICT Research and Applications, 2020)
In this paper, the Stock Exchange Algorithm (SEA), the Product Demand-Availability (PDA) algorithm, and the Affluent and Penurious (AP) algorithm are proposed to solve the power loss reduction problem. In the SEA approach, selling and buying shares in the stock exchange was imitated to design the algorithm. Stockholders are classified as Privileged, Average or Weak based on their fitness value. The PDA optimization algorithm is based on the consumer demand and availability of a product in the market. The Affluent and Penurious algorithm mimics the social behavior of people. The gap parameter (G) is defined to indicate the growing gap between affluent and penurious people when affluent people increase their wealth. The proposed Stock Exchange Algorithm, Product Demand-Availability optimization algorithm and the Affluent and Penurious optimization algorithm were tested in the IEEE 30 bus system. Real power loss minimization, voltage deviation minimization, and voltage stability index enhancement were successfully attained.